The influence of Malaysian Code of Corporate Governance (MCCG) to Enterprise Risk Management (ERM) and value creation - Ghazali, Zahiruddin; Abdul Manab, Norlida (2013)
This study aims to highlight whether the implementation of Malaysian Code of Corporate Governance in 2000 and the revise version in 2007 gives an impact to companies listed in the Malaysian Bourse.Using a standard and reliable variables with acceptable testing methods provide justifiable methodology of testing several aspect of companies specific characteristics. From test result, it is found that MCCG2000 produces more impact compares to MCCG2007 and non-financial companies benefited more compares to finance related companies.